2018
DOI: 10.3847/1538-4357/aadba8
|View full text |Cite
|
Sign up to set email alerts
|

The Environments of the Most Energetic Gamma-Ray Bursts

Abstract: We analyze the properties of a sample of long gamma-ray bursts (LGRBs) detected by the Fermi satellite that have a spectroscopic redshift and good follow-up coverage at both X-ray and optical/nIR wavelengths. The evolution of LGRB afterglows depends on the density profile of the external medium, enabling us to separate wind or ISM-like environments based on the observations. We do this by identifying the environment that provides the best agreement between estimates of p, the index of the underlying power-law … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 90 publications
8
38
2
Order By: Relevance
“…Thus lateral expansion at the speed of sound can still account for the observed late-time decline. Gompertz et al (2018) found a best fit of p = 2.06 ± 0.13 for GRB 160625B, which is consistent with our results in both bands within σ p 13 . In any case, for this burst some form of lateral expansion is required, and the edge effect alone is insufficient.…”
Section: Grb 160625bsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus lateral expansion at the speed of sound can still account for the observed late-time decline. Gompertz et al (2018) found a best fit of p = 2.06 ± 0.13 for GRB 160625B, which is consistent with our results in both bands within σ p 13 . In any case, for this burst some form of lateral expansion is required, and the edge effect alone is insufficient.…”
Section: Grb 160625bsupporting
confidence: 92%
“…A complication was noted by Gompertz et al (2018), who find that using different synchrotron closure relations to estimate p (such as using the spectral index or the pre-or post-break decline) typically results in different estimates, with an intrinsic scatter on the value of p of 0.25 ± 0.04 (we will denote this as σ p ). They argue this is probably caused by emission from GRB afterglows not behaving exactly as the rather simplified analytical models predict 12 .…”
Section: Grb 160625bmentioning
confidence: 99%
“…for this approach (e.g., Maxham et al 2011;Zhang et al 2011), in many studies, the temporal and spectral properties of the GeV extended emission are consistent with the external forward shock model (Kumar & Barniol Duran 2009Ghisellini et al 2010;Beniamini et al 2015;Panaitescu 2017;Gompertz et al 2018;Tak et al 2019).…”
Section: Conditionsupporting
confidence: 55%
“…In later studies, [e.g., 332,333] ISM-like environments continued to be found in long GRB afterglows. Further measurements of the spectral and temporal indices for optical [334] and X-ray [71,[335][336][337] afterglows of long GRBs all point to a split in environment types between wind and ISM.…”
Section: Grb Environments and Grb170817amentioning
confidence: 99%